Correlation of Age, PSA Value, Gleason Score, and Staging with Metastasis in Prostate Cancer - Puti Rania Esfandiary; Ferry Safriadi; Akhmad Mustafa (Majalah Kedokteran Bandung, 2026)
Prostate cancer is the fifth most common cancer among men in Indonesia and carries a substantial risk of metastasis. However, data on prognostic factors such as age, prostate-specific antigen (PSA) value, Gleason score, and local stage among Indonesian patients are still limited. This retrospective cross-sectional study analyzed medical records of prostate cancer patients treated at Dr. Hasan Sadikin General Hospital, Bandung, between 2019–2022. Independent variables were age, PSA value, Gleason score, and local stage; the dependent variable was metastatic status. Data were analyzed using chi-square and multivariate logistic regression tests. A total of 81 patients were included, of whom 44 (54.3%) had metastases. Bivariate analysis showed significant associations of PSA value, Gleason score, and local stage with metastasis (p<0.05). In multivariate analysis, only Gleason score and local stage remained significant independent predictors (p<0.05). The findings indicate that Gleason score and local tumor stage are reliable predictors of metastasis in prostate cancer, while age and PSA are not independent predictors in this cohort. Gleason score and local stage should be prioritized for risk assessment in prostate cancer management in Indonesian hospitals.